People’s People with Sexual Behavior in Street Children - Kusumastuti, Kusumastuti; Herniyatun, Herniyatun; Agustin, Fifi (Proceedings Series on Health & Medical Sciences, 2022)
Street children are children who are excluded, marginal, and excluded from the treatment of affection. Until now the number of street children in Indonesia continues to decline. In 2015 there were 33,400 children, in 2016 there were 20,719 children and in 2017 there were 16,416 children. Objective this research to determine the relationship of the role of peers with sexual behavior in street children. This research used a descriptive correlation method with cross-sectional approach. Data analysis used frequency distribution analysis, Kendall’s tau_b with a significance level of 5%. There results was a relationship between the role of peers and sexual behavior as indicated by Kendall’s tau_b calculation, obtained by Sig. (2-tailed) = 0.013 <0.05 ,. The role of peers in street children in the Karanganyar region was in the bad category of 9 respondents (63.3%), and for sexual behavior in street children in the Karanganyar region in the bad category there were 12 respondents (40%). This conclusion is a relationship between the role of peers and sexual behavior as shown by Kendall’s tau_b calculation, obtained Sig. (2-tailed) = 0.013 <0.05, a sign that there is a relationship between the role of peers and sexual behavior in street children in the Karanganyar region. Recommendation for further researchers, they can research other factors that influence sexual behavior in adolescents and add more samples.